Weapon compartment layout design method for improving the survivability of a naval ship by considering susceptibility distribution based on radar cross section analysis. Issue 2 (12th March 2022) - Hwang, Joon-Tae; Hong, Suk-Yoon; Song, Jee-Hun; Kwon, Hyun-Wung
Abstract: The survivability of a naval ship refers to its ability to withstand the damage caused by enemy attacks and to maintain their missions and functions. During naval warfare, if the armed space of a naval ship is exposed to the enemy, even a single shot can damage the combat system. Therefore, it is important to minimize damage to the armed space of naval ships and improve survivability. In this study, a system was implemented to automate the ship compartment layout design process considering survivability and to derive the optimal compartment layout. The survivability of a compartment can be calculated using the susceptibility distribution obtained using the axis-aligned bounding box (AABB) model and damage ellipsoid volume. To derive the survivability suitable for each naval ship, the susceptibility distribution of the naval ship was derived by radar cross section analysis. In addition, the line distribution space division method was developed to extract the AABB model from the analysis model. A genetic algorithm was used to derive an optimal compartment layout considering survivability. To compare the differences in survivability according to the compartment layout, optimal and worst compartment layout analysis was performed. Graphical Abstract: